Analisis Rekaman Suara Magic Call pada Provider Seluler dengan Rekaman Suara Asli. - M Zulpahmi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Abstract Magic call is a voice changer modification service from the provider that allows you to change the original voice when calling. This study was conducted to analyze the characteristics of the similarity level of magic call voice recordings on Telkomsel and XL providers with original voice recordings for forensic audio purposes. The voice recordings of magic call Telkomsel and XL use 4 voice recording samples consisting of 2 women and 2 men using their original voices. The data were analyzed using pitch, formant, and spectrogram analysis techniques. The data were then extracted using praat and gnumeric tools. The findings in this study showed that the four-voice recordings of 2 women and 2 men from magic call were compared with the original voice recordings showing non-identical results. This can be seen from the analysis results table which shows that 13 words from the sound recordings have very high non-identical values compared to identical values. It can be concluded that the magic call on Telkomsel and XL providers are not identical. Keywords— Forensic Audio, Sound Recording, Provider, Magic Call.